2015
DOI: 10.1186/s13690-015-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy ranking of Canadians among the populations in selected OECD countries and its disparities among British Columbians

Abstract: BackgroundCanada is among the world’s leading nations with the longest life expectancy at birth (LE0), and British Columbia (BC) ranks top among Canadian provinces and territories for LE0 in both men and women. This paper examined recent data as well as projected trends in LE0 of Canadian men and women and explored the geographic and socioeconomic disparities in LE0 specific to BC.MethodsUsing retrospective data on LE0 and age-standardized mortality rates, Canada was compared to 11 other Organization for Econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…[13][14][15][16] While studies clearly showed the differences in life expectancy, little is known about the contributions of cause of death and risk factors associated with sex and SES. In this analysis, we showed that drug overdose deaths alone explained approximately 9% of LE 0 loss in males in 2016, compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] While studies clearly showed the differences in life expectancy, little is known about the contributions of cause of death and risk factors associated with sex and SES. In this analysis, we showed that drug overdose deaths alone explained approximately 9% of LE 0 loss in males in 2016, compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…, 34 , 38 , 40 , 41 Furthermore, our findings may be influenced by a secular trend where overall life expectancy 43 is increasing in recent years. Of particular note, BC has the longest life expectancy in Canada and one of the highest in the world 44 …”
Section: Discussionmentioning
confidence: 99%
“…Introduction L'association entre l'état de santé et le statut socioéconomique (SSE) est largement documentée [1][2][3] . En particulier, les publications scientifiques internationales et canadiennes accumulent de plus en plus de données probantes indiquant que la mortalité toutes causes confondues et la mortalité par cause sont plus élevées chez les personnes ayant un faible SSE, phénomène qui a pu être observé à l'aide de données socioéconomiques individuelles 4-10 comme de données socioéconomiques à échelle fine tenant compte ou non du SSE individuel 4,7,[10][11][12][13][14][15][16][17][18] .…”
Section: Mots-clés : Statut Socioéconomique Disparités En Matière D'unclassified